FINANCING CONTROLS OF A PUBLIC SUPPORT POLICY WITH THE USE OF INFORMATION TECHNOLOGIES AND VARYING COSTS OF SUCH CONTROLS ON THE EXAMPLE OF THE COMMON AGRICULTURAL POLICY (ОБЛІК, ОПОДАТКУВАННЯ І КОНТРОЛЬ: ТЕОРІЯ ТА МЕТОДОЛОГІЯ, 2025)
.